High durability cement electric pole suitable for northwest wind and sand erosion environment

CN122977765APending Publication Date: 2026-10-27NINGXIA HONGHUI CEMENT POLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611180676.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有技术存在以下核心缺陷:常规配比方法默认采用洁净河砂或机制砂作为细骨料,未考虑就地利用西北地区储量丰富的风积沙资源,更未解决风积沙自身携带的可溶性氯盐、硫酸盐在混凝土内部长期析出引发的界面化学劣化风险,同时,常规配比仅以标准养护条件下的抗压强度作为唯一设计控制指标,未涵盖抗风沙冲蚀磨损、抗盐碱离子渗透等西北服役环境所必需的核心耐久性维度,产生上述问题的根本原因在于:一方面,风积沙因含盐量高、粒形较差且存在碱活性波动,长期以来被认为不适宜直接作为混凝土细骨料使用,缺乏对其进行改性处理并实现资源化利用的系统工艺;另一方面,传统混凝土电线杆的设计理念以力学强度为核心,忽略了西北极端环境条件下耐久性指标对材料组成与结构的特殊要求,缺乏从原料预处理、基体增强到表面防护的全链条耐久性提升方案

Benefits of technology

1、本发明采用脱盐、包覆、活化一体化处理工艺改良风积沙,脱盐工序从源头清除可溶性盐离子,阻断混凝土内部长期离子侵蚀通道,纳米偏高岭土包覆层在水泥水化阶段参与二次水化反应,在骨料与水泥石界面区域生成额外水化硅酸钙凝胶,显著提升界面致密程度与粘接强度,将原本易造成侵蚀破坏的风积沙转化为具备界面增强效果的功能性骨料,实现了西北地区储量丰富的风积沙在混凝土电线杆中的高值化利用,无需外购河砂或机制砂,降低材料运输成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application relates to the technical field of cement electric poles, in particular to a high-durability cement electric pole suitable for a northwest wind-sand erosion environment, which comprises the following steps: (1) wind-sand pretreatment: sending northwest wind-sand into a gradient sand washing and desalination machine, the wind-sand is improved by adopting a desalination, coating and activation integrated treatment process, soluble salt ions are removed from the source in the desalination process, the long-term ion erosion channel in the concrete is blocked, a nano meta-kaolin coating layer participates in secondary hydration reaction in the cement hydration stage, additional hydrated calcium silicate gel is generated in the interface area between the aggregate and the cement stone, the interface density and the bonding strength are significantly improved, the wind-sand which is easy to cause erosion damage is converted into functional aggregate with interface enhancement effect, the high-value utilization of the abundant wind-sand in the northwest region in the concrete electric pole is realized, river sand or machine-made sand needs not to be purchased from outside, and the material transportation cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cement utility pole technology, and more specifically, to a highly durable cement utility pole suitable for the wind and sand erosion environment of Northwest China. Background Technology

[0002] Cement power poles play a vital role in power infrastructure construction as the main supporting components of overhead transmission and distribution lines. In Northwest my country, due to the special geographical and climatic conditions such as frequent sandstorms, high soil salinity, and significant diurnal temperature differences, cement power poles are subjected to multiple coupled destructive effects, including sandstorm erosion, salt and alkali ion penetration, and temperature stress. Conventional cement power poles develop problems such as surface peeling, protective layer cracking, and steel reinforcement corrosion after only a few years of service, with a service life far below the design life, seriously threatening the safe operation of the power grid. Currently, the industrial production of cement power poles mainly adopts centrifugal molding technology, using cement, river sand, and crushed stone as basic raw materials to prepare concrete, which is then centrifugally compacted and cured under normal pressure or naturally.

[0003] The existing technology has the following core defects: conventional proportioning methods default to using clean river sand or manufactured sand as fine aggregate, failing to consider the on-site utilization of the abundant aeolian sand resources in Northwest China, and failing to address the risk of interfacial chemical degradation caused by the long-term precipitation of soluble chlorides and sulfates carried by aeolian sand inside the concrete. At the same time, conventional proportioning only uses compressive strength under standard curing conditions as the sole design control index, failing to cover the core durability dimensions necessary for service environments in Northwest China, such as resistance to wind and sand erosion and wear, and resistance to salt and alkali ion penetration. The root cause of the above problems is that, on the one hand, aeolian sand has long been considered unsuitable for direct use as fine aggregate in concrete due to its high salt content, poor particle shape, and fluctuating alkali activity, and there is a lack of systematic processes for modifying it and realizing its resource utilization; on the other hand, the design concept of traditional concrete utility poles focuses on mechanical strength, ignoring the special requirements of durability indicators on material composition and structure under the extreme environmental conditions of Northwest China, and lacking a full-chain durability improvement scheme from raw material pretreatment, matrix reinforcement to surface protection.

[0004] Based on this, the present invention discloses a highly durable cement utility pole suitable for the wind and sand erosion environment of Northwest China. Summary of the Invention

[0005] To address the problems mentioned in the background art, the present invention provides a highly durable cement utility pole suitable for the wind and sand erosion environment of Northwest China, comprising the following steps: (1) Pretreatment of aeolian sand: Northwest aeolian sand is sent to a gradient sand washing and desalination machine, and desalination is carried out by three-stage countercurrent washing to control the residual soluble salt content of aeolian sand to be no higher than 0.03%; the desalinated wet sand is transferred to a slurry coating tank, nano-kaolin slurry is added, and it is stirred at a stirring speed of 40-80 revolutions per minute for 15-30 minutes to form a uniform wet coating layer on the surface of the sand particles. The coated wet sand is sent to a rotary low-temperature activation furnace and calcined at 180℃-280℃ for 50-80 minutes. After cooling, activated modified aeolian sand is obtained; before the wet sand enters the furnace, the waste heat of the flue gas discharged from the rotary low-temperature activation furnace is used to preheat the coated wet sand to reduce the moisture content of the wet sand to 10%-14%.

[0006] (2) Concrete preparation: Prepare the inner layer of high-strength matrix concrete, the outer layer of wear-resistant and wind-resistant sand concrete and the self-healing nano-silicon-based penetrating coating by weight, with 1 part by weight corresponding to 1 kg.

[0007] Preferably, the inner high-strength matrix concrete comprises: 100 parts cement, 180-220 parts activated modified aeolian sand, 15-30 parts fly ash, 5-12 parts silica fume, 3-8 parts calcium sulfoaluminate expansive agent, 1.5-4 parts basalt short-cut fiber, 0.5-1.5 parts polycarboxylate-based high-efficiency water-reducing agent, and 28-40 parts water.

[0008] The outer layer of wear-resistant and wind-sand-resistant concrete comprises: 100 parts cement, 160-200 parts activated modified aeolian sand, 12-25 parts fly ash, 6-15 parts silica fume, 4-10 parts calcium sulfoaluminate-based expansion agent, 2.5-5 parts basalt short-cut fibers, calcium carbonate whiskers, 0.8-2.0 parts polycarboxylate-based high-efficiency water-reducing agent, and 26-38 parts water. The amount of calcium carbonate whiskers is such that the weight ratio to basalt fibers is 0.25-0.40:1, and the calcium carbonate whiskers are added to the concrete mixture in the form of a pre-dispersed suspension slurry.

[0009] When mixing the inner layer concrete, put all the powder materials into a twin-shaft forced mixer and dry mix for 2-3 minutes until they are evenly mixed. Dissolve the polycarboxylate superplasticizer in all the water to make a polycarboxylate superplasticizer aqueous solution, and then add it to the mixer. Wet mix for 3-5 minutes until the slurry is uniform. Then, evenly sprinkle basalt short-cut fibers into the mortar and continue to mix for 2-4 minutes until the fibers are evenly distributed in the slurry and there is no clumping. Control the slump of the discharged material to be 40-60 mm.

[0010] When mixing the outer layer concrete, put all the powder materials into a twin-shaft forced mixer and dry mix until they are uniformly mixed. First, add calcium carbonate whiskers to water accounting for one-third to one-half of the total water volume to pre-disperse and prepare a suspension slurry. Pre-disperse and stir for 3 to 5 minutes. Add the pre-dispersed calcium carbonate whisker suspension slurry, the remaining water, and the polycarboxylate superplasticizer aqueous solution to the mixer and wet mix for 3 to 5 minutes until the slurry is uniform. Then add basalt short-cut fibers and stir for 3 to 5 minutes until the fibers and whiskers are uniformly dispersed in the slurry without obvious agglomerates. Control the slump of the discharge to be 30 to 50 mm.

[0011] Preferably, the self-healing nano-silica-based penetrating coating comprises: 40-60 parts of nano-silica sol, 5-12 parts of silane coupling agent, 3-10 parts of microcapsule repair agent, 20-40 parts of deionized water, and 0.5-2 parts of surfactant. The nano-silica sol, silane coupling agent, deionized water, and surfactant are stirred in a mixing tank at 60-100 rpm for 10-20 minutes until the mixture reaches a homogeneous colloidal state, thus obtaining the coating base liquid. Then, the microcapsule repair agent is slowly added, and the mixture is stirred at a low speed of 30-50 rpm for 15-25 minutes until the microcapsules are uniformly suspended in the base liquid, thus obtaining the self-healing nano-silica-based penetrating coating. The core material of the microcapsule repair agent is composed of calcium sulfoaluminate expanded clinker and sodium carbonate in a weight ratio of 1:0.2-0.4, wherein the calcium sulfoaluminate expanded clinker has calcium sulfoaluminate as its main mineral component. The inorganic material, wherein the wall material of the microcapsule repair agent is a composite shell of urea-formaldehyde resin and nano-silica, and the preparation method of the microcapsule repair agent is as follows: urea and formaldehyde are dissolved in water at a molar ratio of 1:1.5-2.0, the pH value is adjusted to 8-9, and the reaction is carried out at 60℃-70℃ for 1-2 hours to obtain urea-formaldehyde resin prepolymer. Calcium sulfoaluminate expanded clinker and sodium carbonate are mixed and ground in a certain proportion to serve as the core material. Nano-silica dispersion is added and stirred evenly. Under stirring conditions, the urea-formaldehyde resin prepolymer is slowly added to the core material dispersion, the pH value is adjusted to 3-4, and the reaction is continued at 50℃-60℃ for 2-3 hours to allow the urea-formaldehyde resin to polymerize and deposit on the surface of the core material to form the wall material. After washing and drying, the microcapsule repair agent is obtained. The wall thickness is adjusted to 2-4 micrometers by controlling the stirring speed and reaction time, and the average particle size of the microcapsules is 30-60 micrometers.

[0012] Preferably, (3) layered centrifugal molding: using a mold laying machine, the inner layer of concrete is first poured into the mold to the designed thickness of the inner layer, which accounts for 60% to 70% of the total wall thickness of the rod; the variable frequency centrifugal molding machine is started, and at a centrifugal speed of 80 to 120 rpm, it is supplemented with low-frequency vibration of an attached vibrator for 10 to 20 seconds. After the vibration is completed, the outer layer of concrete is laid to the designed thickness of the outer layer, which accounts for 30% to 40% of the total wall thickness of the rod; then the speed is increased to medium speed of 250 to 350 rpm to compact for 3 to 5 minutes, and then high speed of 450 to 600 rpm to orient for 5 to 8 minutes, so that the fibers are oriented in the circumferential direction. After centrifugation, it is left to stand for 10 to 20 minutes. During the high-speed centrifugation stage, the amount of calcium carbonate whiskers discharged from the mold with the centrifugal water is less than 15% of the initial whisker content.

[0013] During the layered centrifugal molding process, the low-speed vibration stage removes interlayer air bubbles, the medium-speed stage achieves overall compaction of the concrete, and the high-speed stage uses centrifugal force to cause fine particles and liquid phases in the outer layer slurry to migrate to the inner layer, forming a component transition zone with a thickness of 0.5 to 2 mm at the interface between the inner and outer layers. This transition zone is formed by the mutual penetration and interlocking of the outer and inner concrete layers.

[0014] Preferably, (4) segmented gradient curing: the molded rod is sent into a programmable curing kiln for three-stage temperature and humidity co-curing. Multiple temperature and humidity sensors are installed in the curing kiln. The steam supply and exhaust volume are monitored in real time and automatically adjusted by a programmable logic controller. The first stage is 40℃~50℃ with a relative humidity of not less than 95% for 2~3 hours. The second stage is heated to 75℃~85℃ at a rate of 10℃~15℃ per hour, and the relative humidity is adjusted to 80%~90% for 4~6 hours. During this stage, the calcium sulfoaluminate expansion agent in the inner and outer concrete layers expands synchronously to compensate for concrete shrinkage. The third stage is cooled at a rate of 10℃ per hour. The surface temperature of the rod and the ambient temperature of the workshop are monitored in real time by a temperature sensor in the kiln. When the temperature difference between the two is not greater than 20℃, the rod is removed from the kiln. The drying shrinkage rate of the concrete after demolding is 150×10 -6 ~180×10 -6 .

[0015] Preferably, (5) Coating spraying: The surface of the cured pole is cleaned and dusted by the concrete pole surface cleaning and preheating unit and preheated to 30℃~35℃. The self-healing nano-silicon-based penetrating coating prepared in step (2) is uniformly sprayed onto the surface of the pole using a high-pressure airless spraying equipment. The coating is applied in two coats with an interval of 40~50 minutes between the two coats. The penetration depth of the coating is 3.5~4.5 mm. The coating is naturally cured for 48~60 hours to form a self-healing protective coating. The self-healing anti-seepage pressure recovery rate of the obtained self-healing protective coating is not less than 80%.

[0016] The present invention also provides a high-durability cement pole prepared by the above preparation method, which has a double-layer gradient structure of an inner high-strength matrix concrete and an outer wear-resistant and wind-sand-resistant concrete. A component transition zone with a thickness of 0.5 to 2 mm is formed between the two concrete layers. The transition zone is formed by an interlocking structure of the outer slurry penetrating into the inner layer. The outer surface is covered with the self-healing nano-silicon-based penetrating coating.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention uses an integrated desalination, coating, and activation process to improve aeolian sand. The desalination process removes soluble salt ions from the source, blocking long-term ion erosion channels inside concrete. The nano-kaolin coating layer participates in the secondary hydration reaction during the cement hydration stage, generating additional hydrated calcium silicate gel at the interface between aggregate and cement stone, significantly improving the density and bonding strength of the interface. This transforms aeolian sand, which is prone to erosion and damage, into a functional aggregate with interface enhancement effects, realizing the high-value utilization of abundant aeolian sand in Northwest China in concrete utility poles. There is no need to purchase river sand or manufactured sand, reducing material transportation costs.

[0018] 2. This invention incorporates a multi-scale hybrid reinforcement system of basalt short-cut fibers and calcium carbonate whiskers into the outer concrete layer. The basalt fibers undertake macroscopic stress transmission and crack bridging, while the calcium carbonate whiskers fill the micron-level pores between the fibers and dissipate the impact kinetic energy of wind and sand particles. Together, they construct a micron- and millimeter-level composite crack-resistant network, comprehensively inhibiting the entire process of microcracks from initiation to extension and connection, thus significantly improving the wear resistance of the concrete surface and greatly reducing the wind and sand erosion wear rate.

[0019] 3. This invention incorporates quantifiable and measurable indicators such as wind and sand erosion abrasion rate, chloride ion diffusion coefficient, sulfate expansion rate, and fiber orientation degree into the mix design and quality control system. It classifies and matches mix proportion schemes according to light, moderate, and heavy wind and sand environments as well as low, medium, and strong saline-alkali environments, so that the design concept of concrete utility poles can be changed from simply meeting the compressive strength standard to adapting to the durability requirements of specific sites, and realizing customized production according to environmental level.

[0020] 4. This invention employs a phased and differentiated temperature and humidity control system for the curing kiln. During the low-temperature stage, high humidity curing prevents surface water loss and shrinkage. During the medium-temperature hardening stage, humidity is gradually reduced to balance the internal and external hydration rates. During the slow cooling stage, slow temperature reduction minimizes thermal shrinkage cracks. After curing, a nano-silicon-based self-healing and penetrating coating is applied. The inorganic silicon component seals the surface capillary pores to form a physical barrier layer. Internal microcapsules release repair substances to actively heal defects when cracks occur. The self-healing and anti-seepage pressure recovery rate reaches over 80%, forming a dual long-term protection system combining barrier and self-healing, significantly extending the safe service life of cement power poles in the combined erosion environment of northwest wind, sand, and saline-alkali soil. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the overall process of the present invention; Figure 2 This is a schematic diagram illustrating the testing of the basic mechanical and durability properties of concrete according to the present invention. Figure 3 This is a schematic diagram of the test results of the inner and outer concrete expansion rates of the present invention; Figure 4 This is a schematic diagram showing the performance test results of the self-healing coating of the present invention. Detailed Implementation

[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example

[0023] Therefore, this invention provides a highly durable cement utility pole suitable for the wind and sand erosion environment of Northwest China. See [link to relevant documentation]. Figure 1 As shown, it includes the following steps: Step 1: Coating and Activation Synergistic Pretreatment of Aeolian Sand for Desalination Aeolian sand collected locally in Northwest China is fed into a gradient sand washing and desalination machine. A three-stage countercurrent rinsing process is used to remove soluble chloride and sulfate. The three-stage countercurrent rinsing means that the aeolian sand is passed through three sets of rinsing tanks connected in series. The flow direction of the rinsing water in each rinsing tank is opposite to the conveying direction of the aeolian sand. The desalination efficiency is improved by using the countercurrent water flow to rinse step by step. After desalination, the residual soluble salt content of the discharged aeolian sand is controlled to be 0.02%. The desalinated wet sand was transferred to a slurry coating tank equipped with a stirring function, and nano-metakaolin slurry with an average particle size of 400 nm and a solid content of 20% was added. The mixture was stirred at 60 rpm for 20 minutes to form a uniform and moist coating layer on the surface of the sand particles. The coated wet sand was then preheated using the waste heat from the flue gas discharged from a rotary low-temperature activation furnace to reduce the moisture content of the wet sand to 12%. It was then sent back to the activation furnace and calcined at 250°C for 60 minutes. The nano-metakaolin coating layer was activated through low-temperature thermal activation. After cooling, the activated modified aeolian sand was obtained. The activation index was determined to be 0.82 using the lime absorption hydrochloric acid selective dissolution method, and the coating coverage rate was determined to be 88% using scanning electron microscopy energy dispersive spectroscopy.

[0024] Step 2: Mixing of double-layer multi-scale fiber-reinforced concrete Weigh all ingredients according to the following specific formula, where 1 part corresponds to 1 kilogram.

[0025] The raw material composition of the inner high-strength matrix concrete is as follows: 100 kg of cement; 200 kg of activated modified aeolian sand, 22 kg of fly ash, 8 kg of silica fume, 5 kg of calcium sulfoaluminate expansive agent, 2.5 kg of basalt short chopped fiber with a fiber length of 12 mm and a single filament diameter of 15 micrometers, 1.0 kg of polycarboxylate-based high-efficiency water-reducing agent, and 34 kg of water.

[0026] The raw material composition of the outer layer of wear-resistant and wind-sand-resistant concrete is as follows: 100 kg of cement; 180 kg of activated modified aeolian sand; 18 kg of fly ash; 10 kg of silica fume; 7 kg of calcium sulfoaluminate-based expansion agent; 3.5 kg of basalt short-cut fiber with a fiber length of 12 mm and a single filament diameter of 15 micrometers; calcium carbonate whiskers, the amount of which meets the weight ratio of basalt fiber to 0.34:1, i.e., 1.2 kg, with an average whisker diameter of 1 micrometer, an average length of 20 micrometers, and an aspect ratio of 20; 1.4 kg of polycarboxylate-based high-efficiency water-reducing agent; and 32 kg of water.

[0027] Inner layer concrete mixing: Activated modified aeolian sand, cement, fly ash, silica fume, and calcium sulfoaluminate-based expansion agent are added to a twin-shaft forced mixer and dry-mixed for 3 minutes until uniformly mixed. Polycarboxylate superplasticizer is dissolved in all water to prepare a polycarboxylate superplasticizer aqueous solution, which is then added to the mixer and wet-mixed for 4 minutes until the slurry is uniform. Basalt short-cut fibers are evenly sprinkled into the mortar, and mixing continues for 3 minutes until the fibers are evenly distributed in the slurry without clumping. The discharge slump is 50 mm.

[0028] Outer layer concrete mixing: Activated modified aeolian sand, cement, fly ash, silica fume, and calcium sulfoaluminate-based expansion agent are added to a twin-shaft forced mixer and dry-mixed until uniform. First, calcium carbonate whiskers are pre-dispersed in water comprising half the total volume to form a suspension slurry. The pre-dispersed slurry is stirred for 4 minutes. The pre-dispersed calcium carbonate whisker suspension slurry, along with the remaining water and polycarboxylate superplasticizer aqueous solution, is added to the mixer and wet-mixed for 4 minutes until the slurry is uniform. Then, basalt short-cut fibers are added evenly and stirred for 4 minutes until the fibers and whiskers are uniformly dispersed in the slurry without obvious agglomerates. The discharge slump is 40 mm.

[0029] Step 3: Layered centrifugal molding The concrete is poured in layers using a mold placing machine: First, the inner layer of high-strength concrete is poured to the designed thickness, which accounts for 65% of the total wall thickness of the rod. The variable frequency centrifugal molding machine is started and rotated at a low speed of 100 rpm, while an attached vibrator performs low-frequency vibration for 15 seconds. The air exhaust effect is controlled by preset vibration time parameters. After vibration, the equipment is kept in a low-speed rotation state, and the outer layer of wear-resistant concrete is evenly laid on top of the inner layer to the designed thickness, which accounts for 35% of the total wall thickness of the rod. Then, the rotation speed is increased in stages: a medium speed of 300 rpm for 4 minutes to achieve overall concrete compaction, and a high speed of 500 rpm for 6 minutes to promote the circumferential orientation of fibers and whiskers. After centrifugation, the mixture is left to stand for 15 minutes. During the low-speed and medium-speed stages, the surface of the inner layer concrete remains moist. During the high-speed stage, the cement paste and fine particles in the outer layer migrate to the interface and intercalate with the inner surface to form a component transition zone.

[0030] In the outer concrete mix, there are 100 kg of cement, 18 kg of fly ash, 10 kg of silica fume, and 32 kg of water. The initial water-cement ratio is 0.25. During centrifugation, some water is ejected, further reducing the actual water-cement ratio. During the high-speed centrifugation stage, due to their micron-sized particle size and viscous resistance, most of the calcium carbonate whiskers remain in the outer concrete matrix. Thermogravimetric analysis was used to determine the amount of whisker loss. It was calculated that the mass of whiskers discharged accounted for 12% of the initial whisker content, meaning the whisker loss was 12%, which is lower than the initial whisker content of 15%.

[0031] The fiber circumferential orientation degree was detected as 0.82 using the cross-sectional image ellipse fitting method, and the uniformity of the outer concrete whisker dispersion was detected as 0.85 using the slurry washing laser particle size analysis method.

[0032] Step 4: Segmented Gradient Curing The molded rods are then fed into a programmable curing kiln. Multiple temperature and humidity sensors are installed inside the kiln, and a programmable logic controller (PLC) monitors and automatically adjusts the steam supply and exhaust volume in real time. A three-stage temperature and humidity co-curing system is employed: the first stage is low-temperature pre-curing at 45℃ and 95% relative humidity for 2.5 hours; the second stage is medium-temperature hardening curing, with the temperature increased to 80℃ at a rate of 12℃ per hour, while the humidity is gradually reduced to 85%, and maintained at a constant temperature for 5 hours. During this stage, the calcium sulfoaluminate-based expansion agent in both the inner and outer concrete layers undergoes a simultaneous expansion reaction, compensating for concrete shrinkage; the third stage is low-temperature slow cooling, with the temperature decreasing at a rate of 10℃ per hour. Temperature sensors inside the kiln monitor the surface temperature of the rods and the ambient temperature in the workshop in real time. The rods are removed from the kiln when the temperature difference reaches 15℃. After demolding, the concrete drying shrinkage rate is measured using a length comparator and found to be 165 × 10⁻⁶. -6 .

[0033] Step 5: Spraying self-healing nano-silicon-based penetrating coating The self-healing nano-silica-based penetrating coating consists of the following raw material composition: 50 parts nano-silica sol; 8 parts silane coupling agent; 6 parts microcapsule repair agent; 30 parts deionized water; and 1 part surfactant. The core material of the microcapsule repair agent is composed of calcium sulfoaluminate expanded clinker and sodium carbonate in a weight ratio of 1:0.3. The wall material is a composite shell of urea-formaldehyde resin and nano-silica, with a wall thickness of 3 micrometers. The average particle size of the microcapsules is 50 micrometers. The preparation method of the microcapsule repair agent is as follows: urea and formaldehyde are mixed in a molar ratio of 1: 1.8 Dissolve in water, adjust the pH to 8.5, and react at 65℃ for 1.5 hours to obtain urea-formaldehyde resin prepolymer. Mix and grind calcium sulfoaluminate expanded clinker and sodium carbonate in a certain proportion to use as core material. Add nano silica dispersion and stir evenly. Under stirring conditions, slowly add urea-formaldehyde resin prepolymer to the core material dispersion, adjust the pH to 3.5, and continue to react at 55℃ for 2.5 hours to allow urea-formaldehyde resin to polymerize and deposit on the surface of the core material to form wall material. After washing and drying, the microcapsule repair agent is obtained.

[0034] Nano-silica sol, silane coupling agent, deionized water and surfactant additives are stirred in a mixing tank at 80 rpm for 15 minutes until the mixture is in a uniform colloidal state. Then, microcapsule repair agent is slowly added and stirred at a low speed of 40 rpm for 20 minutes until the microcapsules are uniformly suspended in the base liquid to obtain the self-healing nano-silica-based penetrating coating.

[0035] After demolding, the surface of the pole was cleaned and dusted using a concrete pole surface cleaning and preheating unit, and preheated to 30°C. A high-pressure airless spraying device was then used for uniform spraying in two coats, with a 45-minute interval between coats. Natural curing was then performed for 48 hours. The nano-silicon component penetrated into the concrete to seal capillary pores, while the microcapsule repair agent remained within the coating and the surface substrate. The coating penetration depth was measured to be 3.8 mm using a cross-sectional silicon elemental line scanning method. A step-by-step pressure penetration test after pre-cracking repair was conducted, and the self-healing impermeability pressure recovery rate was 80%.

[0036] The cement pole prepared in this embodiment has a double-layer gradient structure with an inner high-strength matrix concrete and an outer wear-resistant and wind-sand-resistant concrete. A component transition zone is formed between the two concrete layers, and the outer surface is covered with the self-healing nano-silicon-based penetrating coating. Example

[0037] This embodiment adjusts the inner layer concrete formula based on Embodiment 1, while the remaining procedures are the same as in Embodiment 1.

[0038] The raw material composition of the inner high-strength matrix concrete is as follows: 100 kg of cement, 190 kg of activated modified aeolian sand, 25 kg of fly ash, 10 kg of silica fume, 6 kg of calcium sulfoaluminate expansive agent, 3.0 kg of basalt short chopped fiber with a fiber length of 15 mm and a single filament diameter of 17 micrometers; 1.2 kg of polycarboxylate-based high-efficiency water-reducing agent; and 36 kg of water.

[0039] The outer concrete formula and process parameters are the same as in Example 1. According to the measurement, the whisker loss in this example is 14%, which is lower than the initial whisker content of 15%. Example

[0040] This embodiment adjusts the outer concrete formula based on Embodiment 1, while the remaining procedures are the same as in Embodiment 1.

[0041] The raw material composition of the outer layer of wear-resistant and wind-sand-resistant concrete is as follows: 100 kg of cement; 170 kg of activated modified aeolian sand; 20 kg of fly ash; 12 kg of silica fume; 8 kg of calcium sulfoaluminate-based expansion agent; 4.0 kg of basalt short-cut fiber with a fiber length of 15 mm and a single filament diameter of 17 micrometers; calcium carbonate whiskers, the amount of which meets the weight ratio of basalt fiber to 0.40:1, i.e., 1.6 kg, with an average whisker diameter of 1.5 micrometers, an average length of 25 micrometers, and an aspect ratio of 17; 1.6 kg of polycarboxylate-based high-efficiency water-reducing agent; and 30 kg of water.

[0042] The inner layer concrete formula and process parameters are the same as in Example 1. According to the measurement, the whisker loss in this example is 11%, which is lower than the initial whisker content of 15%.

[0043] Test Example 1: Basic Mechanical Properties and Durability Tests To verify the technical effect of the present invention, concrete specimens were prepared according to the formulas and processes of Examples 1, 2, and 3, and the following comparative examples were set up: Comparative Example 1: In the pretreatment process of aeolian sand, only water washing and desalination were performed, omitting the nano-kaolin slurry coating and low-temperature activation steps. The remaining formula and process were the same as in Example 1.

[0044] Comparative Example 2: No calcium carbonate whiskers were added to the outer concrete formula, and the rest of the formula and process were the same as in Example 1.

[0045] Comparative Example 3: In the curing process, the product was cured at a constant temperature of 80°C and 90% relative humidity for 8 hours, followed by natural cooling. The rest of the formula and process were the same as in Example 1.

[0046] All performance tests were conducted in accordance with national standards GB / T 50081 and GB / T 50082. Test results are available in [link to relevant documentation]. Figure 2 .

[0047] Depend on Figure 2 It can be seen that the 28-day compressive strength of the inner and outer concrete layers in Examples 1-3 is significantly higher than that in Comparative Example 1, while the wind erosion abrasion rate and chloride ion diffusion coefficient are significantly lower than those in Comparative Example 1. This indicates that the synergistic pretreatment process of wind-desalinated sand desalination-coating-activation of the present invention has a significant incremental effect on improving the mechanical and durability properties of concrete compared with simple desalination treatment. Compared with Comparative Example 2, Examples 1-3 have higher compressive strength of outer concrete and significantly lower wind erosion abrasion rate, proving the contribution of calcium carbonate whiskers to reinforcement and erosion resistance at the micron scale. Compared with Comparative Example 3, Examples 1-3 have higher compressive strength of inner and outer concrete layers, lower drying shrinkage, and significantly lower chloride ion diffusion coefficient and sulfate erosion expansion rate, proving that the segmented gradient curing system of the present invention has significant advantages over conventional constant temperature and humidity curing in inhibiting microcrack generation and improving impermeability and erosion resistance.

[0048] Test Example 2: Compatibility Test of Inner and Outer Layer Expansion Deformation To verify the deformation compatibility of the inner and outer concrete layers after using the same type of expansive agent, inner and outer concrete specimens were molded according to the inner and outer concrete formulations of Example 1. Under the segmented gradient curing regime of Example 1, the expansion rate of the inner and outer concrete layers at each curing stage was measured using the length comparison tester. The test results are shown in [reference needed]. Figure 3 .

[0049] Depend on Figure 3 It can be seen that the difference in expansion rate between the inner and outer concrete layers was controlled within 15×10 during each curing stage. -6 The fact that the expansion and deformation of the inner and outer concrete layers are basically synchronized indicates that there will be no interfacial tensile stress due to the difference in expansion, which verifies that the expansion and deformation coordination of the inner and outer concrete layers after using calcium sulfoaluminate-based expansion agents is good.

[0050] Experimental Example 3: Performance Test of Self-Healing Coating Coated concrete specimens were prepared according to the coating formulation and spraying process of Example 1. An uncoated specimen served as Comparative Example 4, and a specimen coated only with a nano-silica-based coating liquid without microcapsules served as Comparative Example 5. The specific method for pre-fabricating and repairing cracks was as follows: A through crack with a width of 0.2 mm was pre-fabricated on the surface of the specimen after the coating had cured using a three-point bending method. The cracked specimen was then statically cured for 7 days at 20℃±2℃ and 60%±5% relative humidity to allow for self-repair. Afterwards, a water resistance pressure test was conducted according to the national standard GB / T 18446. The test results are shown below. Figure 4 .

[0051] Depend on Figure 4It can be seen that the self-healing impermeability pressure recovery rate of the uncoated specimen in Comparative Example 4 is 50%. This recovery rate comes from the self-healing effect of cracks in the concrete matrix itself. The recovery rate of the specimen in Comparative Example 5, which is only coated with nano-silicon-based coating liquid without microcapsules, is also 50%, indicating that the nano-silicon-based coating alone does not have an active repair function. The recovery rate of the coated specimen in Example 1 reaches 80%, which is a net increase of 30 percentage points compared with Comparative Example 4 and Comparative Example 5. This net increase is entirely attributed to the contribution of the microcapsule repair agent in actively healing defects by rupturing and releasing the core material after the cracks are generated. This result proves that the microcapsule repair agent plays a substantial key repair role in the self-healing protective coating of the present invention.

[0052] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0053] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A highly durable cement utility pole suitable for the wind and sand erosion environment of Northwest China, characterized in that, Includes the following steps: (1) Pretreatment of aeolian sand: Northwest aeolian sand is sent to a gradient sand washing and desalination machine, and desalination is carried out by three-stage countercurrent washing. The residual soluble salt content of the aeolian sand is controlled to be no higher than 0.03%. The desalted wet sand is transferred to a slurry coating tank, and nano-kaolin slurry is added. The mixture is stirred at a stirring speed of 40-80 revolutions per minute for 15-30 minutes to form a uniform wet coating layer on the surface of the sand particles. The coated wet sand is sent to a rotary low-temperature activation furnace and calcined at 180℃-280℃ for 50-80 minutes. After cooling, activated modified aeolian sand is obtained. Before the wet sand enters the furnace, the waste heat of the flue gas discharged from the rotary low-temperature activation furnace is used to preheat the coated wet sand to reduce the moisture content of the wet sand to 10%-14%. (2) Concrete preparation: Prepare the inner layer of high-strength matrix concrete, the outer layer of wear-resistant and wind-resistant sand-resistant concrete and the self-healing nano-silicon-based penetrating coating by weight, wherein 1 part by weight corresponds to 1 kg; The inner high-strength matrix concrete comprises: 100 parts cement, 180-220 parts activated modified aeolian sand, 15-30 parts fly ash, 5-12 parts silica fume, 3-8 parts calcium sulfoaluminate expansive agent, 1.5-4 parts basalt short-cut fiber, 0.5-1.5 parts polycarboxylate-based high-efficiency water-reducing agent, and 28-40 parts water. The outer layer of wear-resistant and wind-sand-resistant concrete comprises: 100 parts cement, 160-200 parts activated modified aeolian sand, 12-25 parts fly ash, 6-15 parts silica fume, 4-10 parts calcium sulfoaluminate expansive agent, 2.5-5 parts basalt short-cut fiber, calcium carbonate whiskers, 0.8-2.0 parts polycarboxylate-based high-efficiency water-reducing agent, and 26-38 parts water. The amount of calcium carbonate whiskers is such that the weight ratio to basalt fiber is 0.25-0.40:1, and the calcium carbonate whiskers are added to the concrete mixture in the form of a pre-dispersed suspension slurry. The preparation method of the self-healing nano-silica-based penetrating coating is as follows: 40-60 parts of nano-silica sol, 5-12 parts of silane coupling agent, 20-40 parts of deionized water, and 0.5-2 parts of surfactant are stirred in a mixing tank at a speed of 60-100 rpm for 10-20 minutes until the mixture is in a uniform colloidal state, thus obtaining the coating base liquid; then, 3-10 parts of microcapsule repair agent are slowly added, and the mixture is stirred at a low speed of 30-50 rpm for 15-25 minutes until the microcapsules are uniformly suspended in the base liquid, thus obtaining the self-healing nano-silica-based penetrating coating. The core material of the microcapsule repair agent is composed of calcium sulfoaluminate expanded clinker and sodium carbonate in a weight ratio of 1:0.2-0.

4. The wall material of the microcapsule repair agent is a composite shell of urea-formaldehyde resin and nano-silica. The preparation method of the microcapsule repair agent is as follows: urea and formaldehyde are dissolved in water at a molar ratio of 1:1.5-2.0, the pH value is adjusted to 8-9, and the reaction is carried out at 60℃-70℃ for 1-2 hours to obtain urea-formaldehyde resin prepolymer. Calcium sulfoaluminate expanded clinker and sodium carbonate are mixed and ground in a certain proportion to serve as the core material. Nano-silica dispersion is added and stirred evenly. Under stirring conditions, the urea-formaldehyde resin prepolymer is slowly added to the core material dispersion. The pH value is adjusted to 3-4, and the reaction is continued at 50℃-60℃ for 2-3 hours to allow urea-formaldehyde resin to polymerize and deposit on the surface of the core material to form the wall material. After washing and drying, the microcapsule repair agent is obtained. (3) Layered centrifugal molding: First, pour the inner layer of concrete into the mold to the designed thickness of the inner layer using a mold feeding machine. The designed thickness of the inner layer accounts for 60% to 70% of the total wall thickness of the rod. Start the variable frequency centrifugal molding machine and use an attached vibrator to vibrate at a low frequency for 10 to 20 seconds at a centrifugal speed of 80 to 120 rpm. After the vibration is completed, lay the outer layer of concrete to the designed thickness of the outer layer. The designed thickness of the outer layer accounts for 30% to 40% of the total wall thickness of the rod. Then, increase the speed to medium speed of 250 to 350 rpm to compact for 3 to 5 minutes. Then, use high speed of 450 to 600 rpm to orient for 5 to 8 minutes to orient the fibers along the circumferential direction. After centrifugation, let it stand for 10 to 20 minutes. During the high-speed centrifugation stage, the amount of calcium carbonate whiskers that are discharged from the mold with the centrifugal water is less than 15% of the initial whisker content. During the layered centrifugal molding process, the high-speed stage uses centrifugal force to cause fine particles and liquid phase in the outer layer slurry to migrate to the inner layer, forming a component transition zone with a thickness of 0.5 to 2 mm at the interface between the inner and outer layers. This transition zone is formed by the mutual penetration and interlocking of the outer and inner concrete layers. (4) Segmented gradient curing: The molded rods are sent into a programmable curing kiln for three-stage temperature and humidity co-curing. Multiple temperature and humidity sensors are installed in the curing kiln. The steam supply and exhaust volume are automatically adjusted in real time by a programmable logic controller. The first stage is 40℃~50℃ with a relative humidity of not less than 95% for 2~3 hours. The second stage is to raise the temperature to 75℃~85℃ at a rate of 10℃~15℃ per hour, adjust the relative humidity to 80%~90%, and keep the temperature constant for 4~6 hours. During this stage, the calcium sulfoaluminate expansion agent in the inner and outer concrete layers undergoes a synchronous expansion reaction. The third stage is to cool down at a rate of 10℃ per hour. The surface temperature of the rods and the ambient temperature of the workshop are monitored in real time by temperature sensors in the kiln. When the temperature difference between the two is not greater than 20℃, the rods are removed from the kiln. The drying shrinkage rate of the concrete after demolding is 150×10 -6 ~180×10 -6 ; (5) Coating spraying: The surface of the cured pole is cleaned and dusted by the concrete pole surface cleaning and preheating unit and preheated to 30℃~35℃; the self-healing nano-silicon-based penetrating coating obtained in step (2) is uniformly sprayed by high pressure airless spraying equipment, and after curing, a self-healing protective coating is formed. The self-healing anti-seepage pressure recovery rate of the self-healing protective coating is not less than 80%.

2. A highly durable cement utility pole suitable for the wind and sand erosion environment of Northwest China, prepared by the method described in claim 1, characterized in that: It has a double-layer gradient structure with an inner layer of high-strength matrix concrete and an outer layer of wear-resistant and wind-sand-resistant concrete. A component transition zone with a thickness of 0.5 to 2 mm is formed between the two concrete layers. This transition zone is formed by an interlocking structure of the outer layer slurry penetrating into the inner layer. The outer surface is covered with the self-healing nano-silicon-based penetrating coating.

3. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, is characterized in that: The average particle size of the nano-meta-kaolin in the nano-meta-kaolin slurry in step (1) is 300-500 nm, the solid content of the slurry is 15%-25%, the activation index of the obtained activated modified aeolian sand is 0.78-0.88, and the coating coverage rate is 82%-92%. The activation index is determined by the lime absorption hydrochloric acid selective dissolution method, and the coating coverage rate is determined by the scanning electron microscopy energy dispersive surface statistical method.

4. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, is characterized in that: The average diameter of the calcium carbonate whiskers in step (2) is 0.5-2 micrometers, the average length is 10-30 micrometers, and the aspect ratio is 15-30; the length of the basalt short-cut fiber is 12-15 millimeters, and the diameter of the single filament is 15-17 micrometers; the wall thickness of the microcapsule repair agent is 2-4 micrometers, and the average particle size of the microcapsules is 30-60 micrometers.

5. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, is characterized in that: In step (2), the basalt short-cut fiber weight of the inner concrete layer is 2.5 to 3.0 parts, and the basalt short-cut fiber weight of the outer concrete layer is 3.5 to 4.0 parts.

6. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, is characterized in that: In step (2), when mixing the inner layer concrete, add all powder materials to a twin-shaft forced mixer and dry mix for 2-3 minutes until uniformly mixed. Dissolve the polycarboxylate superplasticizer in all the water to make a polycarboxylate superplasticizer aqueous solution, then add it to the mixer and wet mix for 3-5 minutes until the slurry is uniform. Then, evenly sprinkle basalt short-cut fibers into the mortar and continue mixing for 2-4 minutes until the fibers are evenly distributed in the slurry without clumping. Control the slump of the discharged material to be 40-60 mm. When mixing the outer layer concrete, add all powder materials to a twin-shaft forced mixer and dry mix for 2-3 minutes until uniformly mixed. The mixture is dry-mixed in a standard mixer until homogeneous. First, calcium carbonate whiskers are added to water accounting for one-third to one-half of the total water volume to pre-disperse and prepare a suspension slurry. The pre-dispersed slurry is stirred for 3 to 5 minutes. The pre-dispersed calcium carbonate whisker suspension slurry, the remaining water, and the polycarboxylate superplasticizer aqueous solution are added to the mixer and wet-mixed for 3 to 5 minutes until the slurry is homogeneous. Then, basalt short-cut fibers are added and stirred for 3 to 5 minutes until the fibers and whiskers are evenly dispersed in the slurry without obvious agglomerates. The slump of the discharged material is controlled to be 30 to 50 mm.

7. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, is characterized in that: In step (5), the high-pressure airless spraying is carried out in two coats with an interval of 40 to 50 minutes between the two coats. The coating penetration depth is 3.5 to 4.5 mm, and the coating is naturally cured for 48 to 60 hours.

8. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, is characterized in that: The preparation method also includes production quality control: the fiber circumferential orientation degree after centrifugal molding is 0.81 to 0.85, and the uniformity of the outer layer concrete whisker dispersion is 0.84 to 0.

88.

9. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, is characterized in that: The amount of whisker loss mentioned in step (3) was determined by thermogravimetric analysis.

10. A high-durability cement utility pole suitable for wind and sand erosion environments in Northwest China, as described in claim 1, characterized in that: In the component transition zone formed between the two layers of concrete in the prepared cement pole, the outer layer of slurry and the inner layer of concrete have an interlocking structure.